Evaluating the Use of Printed Resources Based on the Principle of Least Effort: A Study at Razi University - Amin Zare; Soleiman Shafiei; Mohsen Jafari (نشریه مطالعات دانش‌پژوهی)
Purpose: This study investigates the application of the principle of least effort in the usage of printed resources among students at Razi University. The principle posits that actions are performed in ways that minimize effort.Methodology: A quantitative research design employing a survey method was used. Data were collected from 375 students using a structured questionnaire.Findings: The study revealed that the use of printed resources by Razi University students aligns significantly with the principle of least effort. Undergraduate students exhibited greater adherence to this principle compared to postgraduate levels. Statistical analyses, including Pearson’s correlation and multivariate regression, indicated that the principle of least effort significantly predicts printed resource usage.Conclusion: The principle of least effort appears to be a valid framework for understanding students' resource usage behaviors. The findings underscore its importance for library and information center management.Value: This study introduces a novel exploration of the principle of least effort within the Iranian academic context.